Ablative fractional Co2 laser aided delivery of long-acting glucocorticoid in the treatment of acral vitiligo: a multicenter, prospective, self-bilateral controlled study. (19th May 2019) - Liu, Ling; Wu, Yan; Zhang, Jianzhong; Gu, Heng; Luan, Qi; Qian, Linhan; Wang, Yanting; Gao, Lin; Wang, Hongyi; Xiao, Bihuan; Sun, Yan; Li, Houmin; et al.
Abstract: Background: Acral vitiligo often responses poorly to treatments. Objective: To observe whether pretreatment with ablative fractional CO2 laser aiding penetration of compound betamethasone solution plus NB-UVB could improve the response of refractory acral vitiligo. Methods: Subjects with symmetrical and stable acral vitiligo were enrolled in this study. The symmetrical lesions were randomly allocated to experimental and control sides in a subject. The experimental side underwent five sessions, one month apart, of ablative fractional CO2 laser followed by once of a topical painting of compound betamethasone solution, the control side applied topical betamethasone cream once a day; both sides underwent NB-UVB three times per week. The assessment was performed one month following each of the 1st, 2nd, 3rd, and 5th treatment sessions. Results: Two hundred eighty-nine subjects entered the clinical trial and 126 subjects completed the study. The experiment side showed better improvement in repigmentation. Overall response rate (repigmentation percentage ≥10%) of experiment sides was 51.6%, in contrast, that of control side was 35.8%. There were no severe adverse events in all subjects during the trial. Conclusions: A triple method of ablative fractional CO2 laser, topical compound betamethasone solution plus NB-UVB provided an alternative choice for acral vitiligo with remarkable safety profile. Cinical trial registration: This clinical trial has been registered at Chinese Clinical Trial Registry (Registration number: ChiCTR-TRC-12002593)